Prospective, nonrandomized study to evaluate endovascular repair of pararenal and thoracoabdominal aortic aneurysms using fenestrated-branched endografts based on supraceliac sealing zones - Oderich, Gustavo S.; Ribeiro, Mauricio; Hofer, Jan; Wigham, Jean; Cha, Stephen; Chini, Julia; Macedo, Thanila A.; Gloviczki, Peter (Journal of vascular surgery, 2017)
To investigate outcomes of manufactured fenestrated and branched endovascular aortic repair (F-BEVAR) endografts based on supraceliac sealing zones to treat pararenal aortic aneurysms and thoracoabdominal aortic aneurysms (TAAAs). A total of 127 patients (91 male; mean age, 75 ± 10 years old) were enrolled in a prospective, nonrandomized single-center study using manufactured F-BEVAR (November 2013-March 2015). Stent design was based on supraceliac sealing zone in all patients with ≥ four vessels in 111 (89%). Follow-up included clinical examination, laboratory studies, duplex ultrasound, and computed tomography imaging at discharge, 1 month, 6 months, and yearly. End points adjudicated by independent clinical event committee included mortality, major adverse events (any mortality, myocardial infarction, stroke, paraplegia, acute kidney injury, respiratory failure, bowel ischemia, blood loss >1 L), freedom from reintervention, and branch-related instability (occlusion, stenosis, endoleak or disconnection requiring reintervention), target vessel patency, sac aneurysm enlargement, and aneurysm rupture. There were 47 pararenal, 42 type IV, and 38 type I-III TAAAs with mean diameter of 59 ± 17 mm. A total of 496 renal-mesenteric arteries were incorporated by 352 fenestrations, 125 directional branches, and 19 celiac scallops, with a mean of 3.9 ± 0.5 vessels per patient. Technical success of target vessel incorporation was 99.6% (n = 493/496). There were no 30-day or in-hospital deaths, dialysis, ruptures or conversions to open surgical repair. Major adverse events occurred in 27 patients (21%). Paraplegia occurred in two patients (one type IV, one type II TAAAs). Follow-up was >30 days in all patients, >6 months in 79, and >12 months in 34. No patients were lost to follow-up. After a mean follow-up of 9.2 ± 7 months, 23 patients (18%) had reinterventions (15 aortic, 8 nonaortic), 4 renal artery stents were occluded, five patients had type Ia or III endoleaks, and none had aneurysm sac enlargement. Primary and secondary target vessel patency was 96% ± 1% and 98% ± 0.7% at 1 year. Freedom from any branch instability and any reintervention was 93% ± 2% and 93% ± 2% at 1 year, respectively. Patient survival was 96% ± 2% at 1 year for the entire cohort. Endovascular repair of pararenal aortic aneurysms and TAAAs, using manufactured F-BEVAR with supraceliac sealing zones, is safe and efficacious. Long-term follow-up is needed to assess the impact of four-vessel designs on device-related complications and progression of aortic disease.